SUKUK DAN PEMBANGUNAN NEGARA - Fitrianto, Fitrianto (Islamic Economics and Business Faculty of UIN Antasari, 2019)
Abstract: This article describes the contribution of sukuk to development in Indonesia. Sukuk are bonds based on sharia principles. Retail Sukuk is a sharia investment product offered by the government to individual Indonesian citizens, as an investment instrument that is safe, easy, affordable and profitable. Sukuk has a very important contribution in infrastructure development in Indonesia. The Indonesian government issues sukuk, which aims to finance project development, including infrastructure development. The accumulation of SBSN issuance up to February 27, 2019 reached Rp. 1,044.71 T, while the accumulation of 2013 - 2019 Project Financing Sukuk reached Rp. 90.79 T. For more than a decade SBSN has become one of the important financing and Islamic investment instruments in development in Indonesia.Keywords: Sukuk, Investments, Development, InfrastructureAbstrak: Artikel ini menjelaskan kontribusi sukuk terhadap pembangunan di Indonesia. Sukuk adalah obligasi berdasarkan prinsip syariah. Sukuk Ritel adalah produk investasi syariah yang ditawarkan oleh pemerintah kepada individu Warga Negara Indonesia, sebagai instrumen investasi yang aman, mudah, terjangkau, dan menguntungkan.. Sukuk memiliki kontribusi yang sangat penting dalam pembangunan infrastruktur di Indonesia. Pemerintah Indonesia menerbitkan sukuk, yang bertujuan untuk membiayai pengembangan proyek, termasuk pembangunan infrastruktur. Akumulasi penerbitan SBSN sampai dengan 27 Februari 2019 mencapai Rp. 1.044,71 T, sedangkan akumulasi Project Financing Sukuk 2013 ? 2019 mencapai Rp. 90,79 T. Selama lebih dari satu dekade SBSN telah menjadi salah satu instrumen pembiayaan dan investasi syariah yang penting dalam pembangunan di Indonesia.Kata Kunci: Sukuk, Investasi, Pembangunan, Insfrastruktur.